Corrosion resistance analysis of the weld metal of low-alloy high-strength steel considering different alloy compositions - Song, Liang; Peng, Yun; Zhao, Haiyan; Cao, Yang; Fang, Qian (Frontiers in Materials, 2022)
In order to find the low-alloy high-strength steel welded with the strongest corrosion resistance, the corrosion resistance of HSAL weld metal was studied by considering different alloy compositions. Corrosion resistance of alloy compositions of 460, 690, and 980 MPa was analyzed in an atmospheric environment and simulated seawater environment, respectively. The results of the corrosion weight gain test, weight loss test, and Kelvin probe test showed that the HSAL weld metal with 980 MPa alloy composition has the best corrosion resistance in an atmospheric environment. Through seawater immersion and electrochemical testing, it was found that the HSAL weld metal with 980 MPa alloy composition had good corrosion resistance in a simulated seawater environment, the HSAL with 690 MPa alloy composition had medium corrosion resistance, and the HSAL with 460 MPa alloy composition had the lowest corrosion resistance. The corrosion resistance of the weld zone is the best and that of the heat-affected zone is the worst; these findings may be helpful for research in related fields.